STRATEGI PEMBELAJARAN DALAM MENGEMBANGKAN FUNGSI MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK SWASTA PLUS ULUL ILMI ISLAMIC SCHOOL MEDAN MARELAN - Thursina, Zulfa; Marbun, Sariana (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2025)
Learning strategies are a series of action plans carried out to achieve learning objectives. Fine motor skills are activities carried out by children using small muscles involving eye and hand coordination such as wrist muscles and fingers. The role of the teacher as a facilitator, teacher as an innovator, teacher as a motivator, and teacher as an evaluator. This study was conducted with the aim of analyzing direct learning strategies, interactive learning strategies, independent learning strategies, and to analyze the role of teachers as facilitators, the role of teachers as innovators, the role of teachers as motivators, and the role of teachers as evaluators in developing fine motor functions of children aged 4-5 years at Tk Swasta Plus Ulul Ilmi Islamic School Medan Marelan. The research method used is qualitative by using a descriptive approach and data collection techniques through observation, interviews, and documentation. The results of this study revealed that direct learning strategies in developing fine motor functions of children aged 4-5 years at Private Kindergarten Plus Ulul Ilmi Islamic School Medan Marelan have been implemented well, interactive learning strategies in developing fine motor functions of children aged 4-5 years at Private Kindergarten Plus Ulul Ilmi Islamic School Medan Marelan have been implemented quite well, and independent learning strategies in developing fine motor functions of children aged 4-5 years at Private Kindergarten Plus Ulul Ilmi Islamic School Medan Marelan have been implemented well by teachers at Private Kindergarten Plus Ulul Ilmi Islamic School Medan Marelan. And it can be seen that the role of teachers in developing fine motor functions of children aged 4-5 years at Private Kindergarten Plus Ulul Ilmi Islamic School Medan Marelan is very good.